INTERTEKSTUAL DEKONSTRUKTIF TRADISI PEMUJAAN DEWI SRI DAN DEWI LANJAR: KAJIAN EKOFEMINISME DALAM CERITA RAKYAT - Lestari, Citra Rizky (ppjbsip, 2024)
This study examines the depiction of Dewi Sri and Dewi Lanjar through a deconstructive intertextual approach with the perspective of ecofeminism in the oral tradition of Javanese folklore. Oral traditions are the main object of study because they are an important means of in-heriting cultural, ecological, and local values between generations. Dewi Sri is widely known in the agrarian traditions of Javanese and Balinese as the goddess of rice and fertility, who is wor-shipped through various rituals such as Ngarot—a fertility plea ceremony before the planting season. Meanwhile, Dewi Lanjar is respected through the oral traditions of the people of the northern coast of Java, especially in Pekalongan, through rituals and prayers on the beach to pray for the safety of the fishermen and protection from the dangers of the sea. Through intertex-tuality analysis, this study found that Dewi Sri is represented as a symbol of ecological harmony, fertility, and prosperity, showing the role of women as the guardian of the balance between hu-mans and nature. On the contrary, Dewi Lanjar, who in the narrative was initially portrayed as a figure full of sorrow, underwent a transformation into a powerful figure who was empowered in managing the relationship with the marine nature, reflecting women's resilience, transcendence, and adaptation to ecological challenges. The deconstructive approach shows that these two fig-ures form a relationship of meaning that complements each other, opening up space for new readings of the role of women in ecologically oriented Javanese culture. These findings enrich the understanding of ecofeminism in the folklore of the archipelago and affirm the importance of pre-serving oral traditions as a vehicle for ecological and cultural learning.